Dynamics of alveolar bone healing after the removal of orthodontic temporary anchorage devices. (24th January 2019) - Kim, Sung‐Jin; Ha, Young Don; Kim, Eunji; Jang, Woowon; Hwang, Soonshin; Nguyen, Tung; Ko, Ching‐Chang; Choi, Yoon Jeong; Kim, Kyung‐Ho; Chung, Chooryung J.
Abstract : Objective: The aim of this study was to investigate the dynamics of alveolar bone formation and healing pattern after the removal of orthodontic temporary anchorage devices (TADs). Methods: Miniscrews (N = 32) were inserted into the buccal inter‐radicular alveolar bone in beagle dogs. Afterward, miniscrews were removed at different time points during a 13‐week period and six different in vivo fluorescent markers were injected at 1, 2, 6, 8, 10, and 12 weeks. Serial changes in bone apposition at the removal and intact control sites were evaluated using μCT, histology, and bone histomorphometry. Results: Gradual bone apposition at the TAD removal site was noted with bone volume/tissue volume (BV/TV) reaching the level of the control alveolar bone by 7 weeks. Histologically, newly formed woven bone was detected within the removal site which was distinct from the surrounding pre‐existing alveolar bone at 13 weeks. Accelerated mineral apposition rate (MAR) and bone formation rate (BFR) were noted between 2 and 6 weeks in the removal site ( P  < 0.05). Although MAR and BFR gradually decreased after its peak at 2‐4 weeks, BFR in the removal site was still higher than the control site at 10‐12 weeks ( P  < 0.05). Conclusions: Spontaneous bone healing was noted after TAD removal with regional acceleration of MAR and BFR within 2‐6 weeks. However, the removal site was mainly filled with woven bone even after 13 weeks, suggesting a longer healing period is required for the quality of the alveolar bone to reach levels comparable to the surrounding alveolar bone.